A direct test of the unequal-variance signal detection model of recognition memory - Mickes, Laura; Wixted, John T.; Wais, Peter E. (Psychonomic bulletin & review, 2007)
Analyses of the receiver operating characteristic (ROC) almost invariably suggest that, on a recognition memory test, the standard deviation of memory strengths associated with the lures (sigma(lure)) is smaller than that of the targets (sigma(target)). Often, sigma(lure)/ sigma(target) approximately = 0.80. However, that conclusion is based on a model that assumes that the memory strength distributions are Gaussian in form. In two experiments, we investigated this issue in a more direct way by asking subjects to simply rate the memory strengths of targets and lures using a 20-point or a 99-point strength scale. The results showed that the standard deviation of the ratings made to the targets (S(target)) was, indeed, larger than the standard deviation of the ratings made to the lures (S(lure)). Moreover, across subjects, the ratio S(lure)/ S(target) correlated highly with the estimate of sigma(lure)/ sigma(target) obtained from ROC analysis, and both estimates were, on average, approximately equal to 0.80.